Policy uncertainty and corporate credit spreads - Kaviani, Mahsa S.; Kryzanowski, Lawrence; Maleki, Hosein; Savor, Pavel (Journal of Financial Economics, 2020)
We find a significant positive relation between changes in policy uncertainty and changes in credit spreads. Macroeconomic conditions, including general uncertainty, do not explain this result, which also holds when we use instrumental variables to address endogeneity issues. The impact of policy uncertainty is greater for firms that operate in regulation-intensive industries, face high tax rates, or are dependent on government spending. It is also stronger for firms that engage in political activities or rely on external financing. We conclude that policy uncertainty has a significant effect on firms’ borrowing costs, with exposure to government policies representing an important channel.